Assessment of air quality monitoring networks using an ensemble clustering method in the three major metropolitan areas of Mexico - Stolz, Tobias; Huertas, María E.; Mendoza, Alberto (Atmospheric pollution research, 2020)
The spatial representativeness of air quality stations is a crucial factor in monitoring networks for designing and applying adequate air quality control measures. If redundant stations, which duplicate air quality data, want to be avoided in order to optimize and reduce the operational cost of air quality networks, robust methodologies must be applied for identifying redundant stations. Therefore, this study proposes the use of a clustering ensemble method to recognize similar and redundant stations by combining three clustering techniques: principle component analysis, hierarchical clustering, and k-means. The result of the ensemble method is analyzed based on additional information, such as emission sources and the meteorological and topographical conditions of the area of interest. This methodology is applied to the ozone (O3) and particulate matter with an aerodynamic diameter of less than or equal to 10 μm (PM10) time series data, acquired from the air pollutant monitoring systems located in the three main metropolitan areas of Mexico: Mexico City (MCMA), Monterrey (MMA), and Guadalajara (GMA). The findings show that the GMA has a well distributed air quality network with the fewest number of similar stations, as well as the MMA, which presents the same stations clusters for PM10 and O3. In contrast, in the MCMA, a cluster of possible redundant stations is found. Results confirm that the clustering ensemble method represents a reliable tool for identifying similar stations. [Display omitted] •A robust ensemble method was developed to identify similar and redundant air quality stations within monitoring networks.•The clustering ensemble method is based on the application of three clustering techniques, subject to a consensus criterion.•The three largest metropolitan areas of Mexico proved to be useful testbeds for the application of the ensemble method.•The conceptual distinction between redundant and similar air quality stations is introduced to apply the ensemble method.